THE PRESENT AND THE FUTURE OF M-BANKING ACCORDING TO SPANISH BANK CUSTOMERS (Revista Galega de Economía)
The new technologies application in the banking sector recently has shown a great improvement through the introduction of new channels in a multichannel environment. One of the channels lately implemented is the mobile banking. Employing data from 2008 bank clients, we present a description of the Spanish mobile banking customer, outlining his/her perception and preferences regarding the mobile banking services, proposing practical recommendations for the banks, which converts this study in unique and relevant in Spain.Â